EKPLORASI NILAI-NILAI PENDIDIKAN KARAKTER ISLAMI MELALUI AMTSAL AL-QUR’AN - Rahman, Fathur (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Islamic character education is an important aspect of the formation of moral and responsible individuals. This article examines the verses of the Koran, or verses containing parables, as an effective way of Islamic character education. Through this amtsal methodological approach, the Koran is able to convey its messages with significant impact, is effective in providing advice, and is satisfactory in providing warnings. This research intends to reveal the values of character education contained in the sayings of the Koran. The method used in this research is the literature review research method, which involves collecting, analyzing and interpreting information from various relevant literature sources. The results of this research reveal that there are several Islamic character education values that Allah conveys in the Koran through the amtsal method. These values include Sincerity, Wisdom, Avoiding Backbiting, and Saying Kind Words. By understanding and applying these values, individuals can develop into responsible and contributing members of society. This shows that the Koran can be used as an important source in Islamic character education.